Long Term Results of Adult Tonsillectomy for Recurrent Tonsillitis at a Tertiary Referral Hospital in Nepal - KC, Sarita; Dongol, Suman R; Bhattarai, Sriya; Mahaseth, Rajeev K (Journal of Institute of Medicine Nepal, 2021)
Introduction: Chronic recurrent tonsillitis giving rise to frequent fever and disabling sore throat is the commonest indication for tonsillectomy in adults. The study aims to evaluate long term patients’ perceived improvement subjectively as well as parameters of sore throat, fever, and antibiotics use objectively after adult tonsillectomy. Methods: This retrospective cross sectional study was conducted at Department of ENT Head and Neck Surgery, Shree Birendra Hospital from January to May 2021. Preoperative data consisted of medical records of 81 adults who underwent tonsillectomy for recurrent tonsillitis between August 2012 and September 2013. Postoperative data on the same objective parameters were obtained by telephone during March 2021 after 7.5-8.5 years’ interval. In addition, patients were instructed to subjectively express improvement of symptoms after tonsillectomy compared to preoperative symptoms level. Subjective improvement was measured on a scale of 0% - 100%, 0% being no improvement at all to 100% for complete cure. Results: Out of 81 patients, 31 (38.27%) could be interviewed. Twenty-three were male and 8 were female. The age ranged from 18 to 65 and the mean age was 28.39. Of the 31 patients interviewed, the mean frequency of sore throat post tonsillectomy was reduced from 8.61 to 0.23 per year. Preoperatively, overall annual frequency of fever was 3.83, which decreased to 0.25 post tonsillectomy. Similarly, frequency of antibiotics intake was 5.27 per year, which decreased to 0.73 after tonsillectomy. The mean post tonsillectomy subjective improvement was 85.74%. Conclusion: The adult patients with recurrent tonsillitis had significant improvement in objective symptoms after tonsillectomy. More than half of the patients had complete subjective improvement in post tonsillectomy state.